A Novel method for the identification and quantification of weight faltering. Issue 1 (1st January 2021) - Naumenko, Daniel J.; Dykes, James; O'Connor, G. Kesler; Stanley, Zofia; Affara, Nabeel; Doel, Andrew M.; Drammeh, Saikou; Dunger, David B.; Faal, Abdoulie; Ong, Ken K.; Sosseh, Fatou; Prentice, Andrew M.; et al.
Abstract: Objective: We describe a new method for identifying and quantifying the magnitude and rate of short‐term weight faltering episodes, and assess how (a) these episodes relate to broader growth outcomes, and (b) different data collection intervals influence the quantification of weight faltering. Materials and methods: We apply this method to longitudinal growth data collected every other day across the first year of life in Gambian infants ( n = 124, males = 65, females = 59). Weight faltering episodes are identified from velocity peaks and troughs. Rate of weight loss and regain, maximum weight loss, and duration of each episode were calculated. We systematically reduced our dataset to mimic various potential measurement intervals, to assess how these intervals affect the ability to derive information about short‐term weight faltering episodes. We fit linear models to test whether metrics associated with growth faltering were associated with growth outcomes at 1 year, and generalized additive mixed models to determine whether different collection intervals influence episode identification and metrics. Results: Three hundred weight faltering episodes from 119 individuals were identified. The number and magnitude of episodes negatively impacted growth outcomes at 1 year. As data collection interval increases, weight faltering episodes are missed and the duration of episodes is overestimated, resulting in the rate of weight loss and regain being underestimated. Conclusions: This method identifies and quantifies short‐term weight faltering episodes, that are in turn negatively associated with growth outcomes. This approach offers a tool for investigators interested in understanding how short‐term weight faltering relates to longer‐term outcomes.